Photo-thermal characteristics of water-based Fe3O4@SiO2 nanofluid for solar-thermal applications. (11th May 2017) - Khashan, Saud; Dagher, Sawsan; Al Omari, Salahaddin; Tit, Nacir; Elnajjar, Emad; Mathew, Bobby; Hilal-Alnaqbi, Ali
Abstract: This work proposes and demonstrates the novel idea of using Fe3 O4 @SiO2 core/shell structure nanoparticles (NPs) to improve the solar thermal conversion efficiency. Magnetite (Fe3 O4 ) NPs are synthesized by controlled co-precipitation method. Fe3 O4 @SiO2 NPs are prepared based on sol–gel approach, then characterized. Water-based Fe3 O4 @SiO2 nanofluid is prepared and usedto illustrate the photo-thermal conversion characteristics of a solar collector under solar simulator. The temperature rise characteristics of the nanofluids are investigated at different heights of the solar collector, for duration of 300 min, under a solar intensity of 1000 W m −2 . The experimental results show that Fe3 O4 @SiO2 NPs have a core/shell structure with spherical morphology and size of about 400 nm. Fe3 O4 @SiO2 /H2 O nanofluid enhances the photo-thermal conversion efficiency compared with base fluid and Fe3 O4 /H2 O nanofluid, since the silica coating improves both the thermodynamic stability of the nanofluid and the light absorption effectiveness of the NPs. At a concentration of 1 mg/1 ml of Fe3 O4 @SiO2 /H2 O, and with the utilization of kerosene into the solar collector, and exposure for radiation for 5 min, the photo-thermal conversion efficiency has shown an enhancement at the bottom of the collector of about 32.9% compared to the base fluid.